2010
DOI: 10.1007/s11033-010-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls

Abstract: Interleukin-6 (IL-6) is a multifunctional cytokine involved in different physiologic and pathophysiologic processes and plays important roles in the etiology of cancer. The -174G>C polymorphism of the IL-6 gene influences IL-6 transcription and has been implicated in cancer risk. However, published data have been conflicting. To derive a more precise estimation of the relationship, a meta-analysis of 29,377 cancer cases and 37,739 controls from 50 published case-control studies was performed. Odds ratios (ORs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 63 publications
2
19
1
2
Order By: Relevance
“…Also, genomic analysis did not reveal a difference between bladder cancer patients and healthy controls in allelic frequency at the -174 position for IL-6 gene promoter. This result is compatible with the four met-analysis of IL-6 -174G>C polymorphism and cancer risk (Xu et al, 2011;Liu et al, 2012;Yu et al, 2012;Zhang et al, 2012). However, this null association could be due a lack of consideration for the potential role of the environment; in other words, the gene-environment interaction role in cancer risk, as mentioned by Liu RY et al (Liu et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Also, genomic analysis did not reveal a difference between bladder cancer patients and healthy controls in allelic frequency at the -174 position for IL-6 gene promoter. This result is compatible with the four met-analysis of IL-6 -174G>C polymorphism and cancer risk (Xu et al, 2011;Liu et al, 2012;Yu et al, 2012;Zhang et al, 2012). However, this null association could be due a lack of consideration for the potential role of the environment; in other words, the gene-environment interaction role in cancer risk, as mentioned by Liu RY et al (Liu et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review and meta-analysis of 7 studies inferred that IL-6 -174G/C polymorphism was associated with an increased prostate cancer risk (Zhang et al, 2012b). A meta-analysis involving 29, 377 cases and 37, 739 controls believed that IL-6-174G/C polymorphism was associated with bladder cancer risk (Xu et al, 2011). A case-control study suggested that IL-6 -174G/C polymorphism was associated with the risk of squamous cell esophageal cancer (Upadhyay et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 gene presents two biallelic polymorphisms at positions -174 and -572 in its promoter region (Huang et al, 1999;Bennermo et al, 2004). It had been found that IL-6 promoter polymorphisms (-174G/C and -572G/C) were associated with various risks of cancers (Xu et al, 2011;Magalhaes et al, 2013). It was recently suggested that the IL-6 gene polymorphisms at positions -174 and -572 might increase the risk of gynecological malignancies, including cervical cancer (Nogueira de Souza et al, 2006;Castro et al, 2009;Gangwar et al, 2009;Shi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que o polimorfismo estudado no gene que codifica a IL6 está estritamente relacionado com a propensão a doença, além disso, o alelo dito de risco é responsável por aumentar a produção destas citocinas associando-as a processos inflamatórios, um fator na promoção da carcinogênese (ZHOU et al, 2015;JIA et al, 2015). O aumento dos níveis séricos desta interleucina no organismo pode aumentar o potencial metastático de células cancerosas através de mecanismos como hiper-regulação da expressão de receptores de células endoteliais, e pelo estimulo de fatores de crescimento (XU et al, 2011).…”
Section: Resultsunclassified
“…Tal citocina representa um mediador pró-inflamatório, multifuncional envolvido em diferentes processos fisiológicos e patofisiológicos (XU et al, 2011). É uma citocina pleiotrópica e imunomodulatória secretada pelas células epiteliais das vias aéreas, macrófagos alveolares, adipócitos e miócitos, assim como outros tecidos e células (HE et al, 2009).…”
Section: Fundamentação Teóricaunclassified